Identification of Plankton Species and Environmental Parameters in Lhok Bubon Coastal Waters, Aceh Barat - Wahyuni, Sri; Mursawal, Asri; Samudra, Arung; Rizqi, Miftahul; Ananda, Eva Ersia; Ramadhan, Azhari (Tropical Marine Environmental Sciences, 2026)
Plankton plays a crucial role in aquatic ecosystems as primary producers and bioindicators of water quality. However, baseline information on plankton composition and environmental conditions in the coastal waters of Lhok Bubon, Aceh Barat, remains limited. This study aimed to identify plankton taxa and assess environmental parameters in the study area. Field sampling was conducted in October 2025 at three stations, with three replicates per station. Plankton samples were collected using a plankton net, preserved with Lugol’s solution, and identified under a light microscope based on morphological characteristics. Water quality parameters, including temperature, pH, salinity, and dissolved oxygen (DO), were measured in situ. A total of 10 plankton taxa were identified, dominated by phytoplankton from the class Bacillariophyceae, followed by Cyanophyceae, zooplankton, and other microorganisms. The presence of diatoms such as Aulacoseira granulata and Synedra ulna indicates favorable conditions for primary productivity. Environmental parameters remained relatively stable, with temperature ranging from 31.4 to 32.9°C, salinity from 30 to 34 ppt, pH around 8.27, and DO averaging 11.45 mg/L, all within suitable ranges for aquatic life. The results indicate that Lhok Bubon coastal waters are in relatively good condition and capable of supporting plankton growth and ecological processes. However, the presence of cyanobacteria and organically associated microorganisms suggests the need for continuous monitoring to maintain environmental quality